Combining export processing zones and regional free trade agreements : lessons from the Mexican experience - Sargent, John (2001)
Discusses a number of the generic trade and regulatory conflicts that may result when an attempt is made to combine regional free trade agreements (RFTAs) and export processing zones (EPZs). Presents the two competing models of how EPZ firms can respond to these conflicts. Reviews the changes in trade and investment patterns between the United States and Mexico since the implementation of NAFTA in 1994.